Relationship between T and u in ∇T for other types of summability - Ouadah, Chourouk; Mezrag, Lahcen: Supervisor; Talleb, Abdelhamid: Co-Supervisor. (Mohamed Boudiaf University of Msila, Faculty of Mathematics and Computer Sciences, Department of Mathematics, 2024)
In this memory, we introduce and study the notions of summability in the sublinear case. We prove some characterizations in terms of a domination theorem and some properties of this notions.we are interested in studying the relationship between T and its subdifferential ∇T (the set of all bounded linear operators u : X −→ Y such that u(x) ≤ T(x) for all x in X) ; concerning certain notions of Lipschitz summability.
Keywords: Banach lattice; Lipschitz p-dominated operator; Lipschitz p-summing operator; p-summing operator; subl